Comparative Study of Ischemic Stroke in Patients Aged Above and Below 50 Years Admitted to a Tertiary Care Hospital in Ulaanbaatar - Tsagaankhuu, Delgermaa; Guntev, Tsagaankhuu; Dashjamts, Tuvshinjargal; Gongor, Baigalmaa; Avirmed, Tovuudorj (Central Asian Journal of Medical Sciences, 2016)
Objectives: The aim of this study was to compare characteristics of ischemic stroke between young (20-49 years) and old (50-89 years) patients undergoing investigations and treatment according to one common protocol in a tertiary hospital. Methods: This hospital-based prospective study included 90 young and 130 old patients with acute ischemic stroke. Data regarding the etiology of the stroke, diagnostic test results and degree of functional improvement of patients were examined during their observation. Results: Common causes for stroke in the young patients were current smoking (53.3%), heavy alcohol consumption (51.1%), cardiac embolism (36.0%), migraine with aura (25.5%), infective diseases (15.6%), and oral contraceptive use (14.4%). Leading causes for ischemic stroke in old patients were the conventional risk factors such as hypertension (75.4%), atherosclerosis (66.9%), and diabetes mellitus (26.9%). Most of the young stroke patients demonstrated good functional outcomes, at the time of discharge (71.1%) and at three weeks (86.6%) according to the Rankin Scale. Conclusion: There are significant differences between young and old patients with ischemic stroke regarding to risk factors, etiological subtypes and improvement of functional deficits associated with the stroke.